(untitled) (Journal of Policy and Planning, 2025)
Expanding Health Insurance to Zambia’s informal sector is vital for achieving Universal Health Coverage (UHC) by 2030. However, challenges arise in collecting premiums from dispersed workers with irregular incomes in the informal sector. A mixed-method cross-sectional study in Kazungula District surveyed 384 informal workers and interviewed 10 key informants. Results showed 77.6% were willing to pay for health insurance, with an average contribution of K28.4 (1.85 exchange rate at the time of the study). Factors influencing willingness included age, marital status, income, prior illness, and willingness to enroll. Although awareness was generally high, respondents reported insufficient information to make informed choices. Importantly, the mean amount they were willing to pay was below NHIMA’s required premium, highlighting the need for more affordable and flexible contribution structures. Overall, the study indicates strong potential for expanding insurance coverage among informal sector workers, provided affordability and information gaps are addressed.